Pengembangan Kurikulum dan Program Pendidikan Proses Pengembangan Kurikulum, Desain Program Pendidikan dan Penyesuaian dengan Kebutuhan Siswa - Latifatul Azizah; Sunarto Sunarto (Reflection : Islamic Education Journal, 2025)
The development of the times influences the education system, including the curriculum, which serves as the foundation for achieving educational goals. This article discusses the importance of the curriculum in enhancing the quality of education, particularly in Islamic Education (PAI), as well as how the curriculum is designed to address societal challenges and student needs. This research employs a qualitative approach and descriptive methods to gather information related to curriculum development, which consists of planning, implementation, and evaluation. The curriculum is dynamic and contextual, emphasizing the involvement of relevant parties in adjustments according to social and cultural conditions. The article also explains the design of educational programs, which includes objectives, content, learning experiences, and evaluation, as well as the principles that must be adhered to in curriculum design. Thus, the role of teachers as educators and implementers of the curriculum significantly impacts the quality of learning, making the collaboration between education policy and field practice a key factor in achieving educational success.